Pengaruh Neuromarketing dan Lifestyle Terhadap Impulsive Buying Produk Kamera Analog (Studi pada Komunitas Bersoreria Medan) - Muhammad Balkis Venserjude; Hafiza Adlina; Onan Marakali Siregar (INDO PUBLISHING, 2026)
The use of analog cameras has resurged in recent years, particularly among creative communities such as the Bersoreria Medan Community. Analog cameras are no longer used solely as photographic tools but have become part of visual identity, self-expression, and lifestyle. This trend encourages impulsive buying behavior, especially when consumers are exposed to strong marketing stimuli through social media and community activities. This study aims to analyze the influence of neuromarketing and lifestyle on impulsive buying of analog camera products, both partially and simultaneously, among members of the Bersoreria Medan Community. This research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to 68 respondents and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that neuromarketing and lifestyle have a positive and significant effect on impulsive buying behavior. Simultaneously, both variables contribute 79.4% to impulsive buying behavior. These findings confirm that cognitive, emotional, and lifestyle factors play an important role in encouraging impulsive purchases of analog cameras